(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
This article examines the distinctive characteristics of translating the most complex lexical layers in the translation process: barbarisms, jargons, slang, euphemisms, and taboo words. The study analyzes the functional roles of these lexical units within literary texts, as well as the linguistic and cultural challenges that arise when rendering them from one language to another. Furthermore, the author provides practical recommendations on strategies for maintaining semantic equivalence, preserving stylistic nuances, and implementing cultural adaptation when translating this “complex” vocabulary.